2013
DOI: 10.1128/aac.01590-13
|View full text |Cite
|
Sign up to set email alerts
|

A Novel C5a-Derived Immunobiotic Peptide Reduces Streptococcus agalactiae Colonization through Targeted Bacterial Killing

Abstract: dStreptococcus agalactiae (group B Streptococcus [GBS]) is a Gram-positive bacterium that colonizes the cervicovaginal tract in approximately 25% of healthy women. Although colonization is asymptomatic, GBS can be vertically transmitted to newborns peripartum, causing severe disease such as pneumonia and meningitis. Current prophylaxis, consisting of late gestation screening and intrapartum antibiotics, has failed to completely prevent transmission, and GBS remains a leading cause of neonatal sepsis and mening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Even though several research works have demonstrated the in vitro effects of vaginal lactobacilli on S. agalactiae (Bodaszewska et al , 2010; Juárez Tomás et al ; 2011; Ruiz et al , 2012), the in vivo effect of lactobacilli on this genital pathogen has not been assessed up to now. Cheng et al (2005) and Cavaco et al (2013) used murine models of S. agalactiae vaginal colonization to evaluate the effect of a bacteriophage lytic enzyme and an immunobiotic peptide. Both studies evidenced a reduction in S. agalactiae vaginal colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Even though several research works have demonstrated the in vitro effects of vaginal lactobacilli on S. agalactiae (Bodaszewska et al , 2010; Juárez Tomás et al ; 2011; Ruiz et al , 2012), the in vivo effect of lactobacilli on this genital pathogen has not been assessed up to now. Cheng et al (2005) and Cavaco et al (2013) used murine models of S. agalactiae vaginal colonization to evaluate the effect of a bacteriophage lytic enzyme and an immunobiotic peptide. Both studies evidenced a reduction in S. agalactiae vaginal colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriostatic synthetic polymers may represent a barrier for selectively blocking GBS adherence to the vaginal mucosa, while allowing normal constituents of the vaginal flora, such as lactobacilli, to persist ( 268 ). Recently, a synthetic peptide mimicking human C5a was shown to be directly bacteriocidal toward GBS and displayed therapeutic in vivo activity in both peritonitis and vaginal colonization mouse models ( 269 ). Although these compounds show preclinical efficacy in controlling GBS in animal models, it has yet to be established if any of them are feasible or cost-effective for human use.…”
Section: Alternative Targeted Prevention Strategies Against Gbs Colonmentioning
confidence: 99%
“…Studies on GBS that have used fluorescence approaches to label the bacteria have principally applied labeling methods that incorporate DNA stains, such as LIVE/DEAD viability stains (23,(44)(45)(46)(47)(48)(49), nonspecific protein stains, such as fluorescein isothiocyanate (FITC) (17,(50)(51)(52)(53), or antibody-based immunostaining methods (12,54,55). Other previous studies have reported the expression of GFP in GBS, as follows: Périchon et al (11).…”
Section: Discussionmentioning
confidence: 99%